2014
DOI: 10.1007/s00405-014-3219-8
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of magnesium in post-tonsillectomy patients: a prospective randomised clinical trial

Abstract: The aim of this study was to assess the analgesic, bleeding and nausea/vomiting effects of magnesium with and without metamizol on post-tonsillectomy patients. This prospective and randomised clinical trial included 54 patients aged 18-63 years who were scheduled for elective tonsillectomy. The patients were randomly divided into two groups and administered either magnesium with metamizol or only metamizol. They had been classified as physical status class I and II using the American Society of Anesthesiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
2
10
1
Order By: Relevance
“…In accordance with the literature, no significant relationship was found between PTH and smoking [34], regular alcohol consumption, diabetes, hypertension [35], antihypertensive therapy, postoperative pain medication with NSAIDs (COX1 inhibitor) [8,36] or opioids [8], application of glucocorticoids [8,37], therapy with antibiotics [10,38], duration of hospital stay [24,39] and surgeon experience [15]. The only significant risk factor for PTH was being male, which is in line with other research groups [6][7][8][9][10][11][12][13], although others did not find a significant correlation [14][15][16][17][18]. A sex hormone-dependent and independent mechanism may be involved, as TE/abscess-TE are performed at a median patient age of 26 and 30, respectively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In accordance with the literature, no significant relationship was found between PTH and smoking [34], regular alcohol consumption, diabetes, hypertension [35], antihypertensive therapy, postoperative pain medication with NSAIDs (COX1 inhibitor) [8,36] or opioids [8], application of glucocorticoids [8,37], therapy with antibiotics [10,38], duration of hospital stay [24,39] and surgeon experience [15]. The only significant risk factor for PTH was being male, which is in line with other research groups [6][7][8][9][10][11][12][13], although others did not find a significant correlation [14][15][16][17][18]. A sex hormone-dependent and independent mechanism may be involved, as TE/abscess-TE are performed at a median patient age of 26 and 30, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…In males, increased risk of post-tonsillectomy hemorrhage (PTH) was shown in most studies [6][7][8][9][10][11][12][13], whereas others were not able to find this effect [14][15][16][17][18]. Gender-specific genes contribute to genetic predisposition toward specific diseases.…”
Section: Introductionmentioning
confidence: 99%
“…(15) Many literatures mentioned that postoperative pain should be minimized not only for the patients comfort but also the pain usually impair swallowing with a great risk of dehydration, infection and secondary hemorrhage. (16) Generally in the present study, we found that postoperative pain score in the laser group was slightly greater in CO 2 laser tonsillectomy group with no statistical significant difference and this observation came in agreement to data of Auf et al 1997 who reported that laser tonsillectomy caused more postoperative pain than conventional blunt dissection. (17) Also, according to the Malaysian study by Ishlah et al, the total post operative pain was not significantly different between the two groups .…”
Section: Discussionsupporting
confidence: 82%
“…Painless surgery remains a great aimand should allow a more early back return to normal diet and daily activity with excellent outcome. (3) Post tonsillectomy pain is a problem that the magnitudeof pain in the postoperative period varies as it may be more intense in early morning and reduces during the rest of the day with analgesic medication andkeeping throat moist by cold fluidbut sometimes pain worsens again in the evening, especially during the first three days with swallowing (4) Referred otalgiawith swallowing usually occurred due to common 9 th sensory nerve innervation for both ear and throat that is relieved with regular doses of pain control given every 4 to 6 hours especially in the first 2 to 3 days.. (5) Conventional dissection technique for tonsillectomy operation had the advantage that it is a safe procedure with fewer incidence for post operative complications as bleeding with the possibility for the tonsil can be removed in toto without any remnants and remained the standard procedure for tonsillectomy for many years till now (6) CO 2 Laser tonsillectomy is done with wavelength of 10.6 2 micron is at the peak of absorption of water. This is important to concentrate the energy with little heat to dissipate to adjacent tissues and minimal damage to surrounding structures with minimal edema that focused to create a precise cut and defocused to produce coagulation of small blood vessels so it Fahd Ali Alharbi and Mohamed Rifaat Ahmed: Postoperative Pain After Tonsillectomy; Comparison Between CO 2 Laser Versus Conventional Dissection Tonsillectomy gives clear bloodless field during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the fact that it was not designed to show safety of metamizol, the administered dose was 500 mg two times per day. In this low dose no bleeding risk was found [11].…”
mentioning
confidence: 96%